Potencjał kampowej dekonstrukcji. Przypadek „Kamieni na szaniec” Roberta Glińskiego - Filipak, Agnieszka Tamara; Ratajska, Patrycja (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2015)
In accordance with Susan Sontag’s thesis on camp, camp is purely in the eye of the beholder, with its unconscious and innocent use considered to be the most perfect realization of the concept. This article is an attempt of camp-oriented interpretation and analysis of the film “Kamienie na Szaniec” (Stones for the Rampart; 2014) directed by Robert Gliński, which has the characteristics of camp: it is overaesthetic, stylistically inconsistent, inaccurate, filled to the brim with abuse and artificiality. Nowadays, film is one of the most important mediums of memory, with a significant influence on collective memory. At the same time film is subject to certain restrictions that often transfigure it more to a tabloid and, as a consequence, its use frequently leads to the tabloidization of collective memory. The use of camp as a tool allows (us? People? The viewer? we need a subject here) to perceive the dangers and pitfalls inherent in so transformed a collective memory. Moreover, camp enables exposure and deconstruction of myths and phantasms that govern the mechanisms of that collective memory and thereby may become a catalyst for change.